Spatiotemporal Variation on Fertility, Mating System, and Gene Flow in Vriesea gigantea (Bromeliaceae), an Atlantic Forest Species - Paggi, Gecele Matos; Palma-Silva, Clarisse; Zanella, Camila Martini; Goetze, Márcia; Büttow, Miriam Valli; Lexer, Christian; Bered, Fernanda (Frontiers in Forests and Global Change, 2022)
Knowledge of the patterns of variation in plant mating systems and fitness, in the context of conservation biology, is essential for understanding microscale differences and their probable causes. The aim of this study was to assess the patterns and determinants of spatiotemporal variation in fertility, mating systems, and gene flow in the iconic epiphytic bromeliad Vriesea gigantea, which is endemic to the Atlantic Forest. We studied three wild populations over two years in terms of flowering, fruit set, seed production, and seed germination, and used nuclear microsatellite markers to analyse variations in the mating system and contemporary gene flow. We observed high fertility parameter values, with among-population differences only in fruit set and germination rate. Mating system analysis showed moderate outcrossing rates (tm), which ranged from 0.107 to 1.2, and strong pollen pool genetic structures (ФFT), of 0.319 to 0.598 across populations and years. We suggest that the observed spatiotemporal variation in fertility, mating systems, and gene flow in this iconic and ecologically important rainforest species are attributable to the adaptation to selfing due to edge effects, mainly caused by range expansion during post-glacial migration. Populations on the edge of the V. gigantea distribution were the most genetically divergent in the southern limit of the Atlantic Forest biome. Our results may contribute to ongoing debate regarding the characteristic fitness trade-offs that shape variation in plant mating systems and gene flow when species meet their range limits.